INDONESIAN HIGH SCHOOL STUDENTS’ DEMOTIVATING FACTORS IN LEARNING ENGLISH - Muhammad Rafakhansyah Satria Putra; Ista Maharsi (Universitas Wiralodra, 2023)
Demotivation is a condition that occurs when a person begins to lose motivation or enthusiasm to do something and achieve specific goals. This demotivating condition can occur in various aspects of life, one of which is related to study. This study is aimed to investigate the demotivation factors of EFL High School students in learning English. Two students from a public high school in Indonesia were interviewed. The data were collected using two session interviews. The first session interview was about the external demotivation factors, and the second was about the internal factors of demotivation. Data were analyzed using thematic analysis in which prominent themes were determined based on the frequency of their emergence. This study found two factors influencing students’ demotivation: external and internal. The external factors include teacher factors, attitudes towards peers, negative attitudes towards the target language and everything related to the target language, the target language as a compulsory subject, and textbooks and teaching materials. As for the internal factors, there are low self-esteem and a lack of self-confidence and interest. This study encourages teachers to create a supportive learning atmosphere and adjust teaching practices to minimize learning demotivation.